Relevance of Plasma Obestatin and Early Arteriosclerosis in Patients with Type 2 Diabetes Mellitus - Peng-ying Gu; Dong-mei Kang; Wei-dong Wang; Yan Chen; Zhi-hong Zhao; Hui Zheng; Shan-dong Ye (Journal of Diabetes Research)
We investigated the correlation between obestatin and metabolic parameters and carotid intima-media thickness (IMT) in plasma of patients with type 2 diabetes mellitus (T2DM). We collected 103 patients aged from 60 to 83 years (69.26 ± 5.83 years) form January, 2007 to May, 2009. All patients were divided into normal glucose tolerance (NGT), impaired glucose tolerance (IGT), and T2DM according to the oral glucose tolerance test (OGTT). We found that higher levels of fasting insulin (Fins), fasting blood glucose, 2 h OGTT glucose, homeostasis model assessment of insulin resistance (HOMA-IR), low density lipoprotein cholesterol, glycated haemoglobin, and C-reactive protein (CRP), as well as lower obestatin level and higher intima-media thickness level (IMT), existed in T2DM group compared with NGT group and IGT group (P<0.01). Also, obestatin level was independently associated with HOMA-IR and CRP, while IMT level was independently associated with HOMA-IR, triglyceride, Fins, and obestatin (P<0.01), based on stepwise multiple regression analysis. Therefore, we deduced that the low level of plasma obestatin might be related to early arteriosclerosis in patients with T2DM via increasing IMT level, and elevated plasma obestatin levels might protect T2DM patients against carotid atherosclerosis to some extent.